The impact of EU public procurement regulations on tenders in Spain: a study with adalimumab - Esplugues, F. J.; Andújar, I.; Esplugues, J. V. (Frontiers in Pharmacology, 2024)
Introduction Pharmaceutical spending accounts for a significant portion of public healthcare budgets. To manage these costs, EU countries implement various cost-containment policies, including competitive tendering for pharmaceuticals. This study examines the impact of EU public procurement regulations on medication procurement practices. Methods A search for all published tenders of adalimumab in Spain from 2018 to 2024 in the Spanish Public Sector Procurement Database, a period that coincides with the implementation of European legislation and the emergence of adalimumab biosimilars. All available documentation for each tender was reviewed, including the tender offer, technical specifications, specific administrative clauses, appointments of evaluation commissions, supporting memorandum, and evaluation reports. Results and Discussion Our findings reveal substantial price reductions following the introduction of adalimumab biosimilars, yet highlight significant variability in tender criteria and practices across different regions. Despite adherence to EU directives, the inconsistent application of economic and non-economic factors and an erratic criteria concerning price undermine the intended balance of quality and cost, complicating procurement processes and potentially affecting the availability of a given treatment for patients.